Shoot growth chronology of alpine dwarf pine (Pinus pumila) in relation to shoot size and climatic conditions: a reassessment - Takahashi, Koichi (National Institute of Polar Research, 2006)
P(論文) Shoot growth chronology of alpine dwarf pine (Pinus pumila) was examined near the summit of Mount Norikura in central Japan, in relation to shoot size and climatic conditions. Shoot growth was investigated in 70 shoots with various shoot lengths between 18 and 273cm, and the examined 70 shoots were divided into three size classes (shoot length <70cm, 70-140cm, and >140cm). A shoot growth chronology was developed for each of the three size classes, but was not statistically different among them. It is suggested that the size dependency of shoot growth chronology was rather weak or negligible. Thus, a single shoot growth chronology was developed again, irrespective of shoot size. Climatic factors affecting the shoot growth were analyzed by using monthly climatic data (mean temperature, insolation duration and sum of precipitation). The shoot growth chronology was positively correlated with the June temperature of the current year, suggesting that the high temperature of this month increases the shoot growth by prolonging the growing season. The shoot growth chronology was also positively correlated with the temperatures from July to October of the previous year, suggesting that the growth of P. pumila largely depends on the photosynthetic production of the previous year. The mean temperature during July to October of the previous year explained 30% of the variation of the shoot growth chronology. These results showed that the shoot growth of P. pumila is largely regulated by temperature during the growing season, irrespective of shoot size. departmental bulletin paper